Factorise :-
a)25a^2b^2 - 49c^2
b)p^8 - q^8
give full answer
❎no spams ❎
Answers
Answered by
2
Hey friend
राधे राधे
FACTORISE-:-:-:
1. 25a²b²- 49c²
By id. [ (x+y)(x-y) ] = [x²-y²]
=> (5ab+7c)(5ab - 7c)
2. p^8 - q^8
By id. [ (x+y)(x-y) ] = [x²-y²]
=>[p⁴+q⁴][p⁴-q⁴]
Be perfectionist
राधे राधे
FACTORISE-:-:-:
1. 25a²b²- 49c²
By id. [ (x+y)(x-y) ] = [x²-y²]
=> (5ab+7c)(5ab - 7c)
2. p^8 - q^8
By id. [ (x+y)(x-y) ] = [x²-y²]
=>[p⁴+q⁴][p⁴-q⁴]
Be perfectionist
arnab2261:
need more, buddy..
Answered by
3
Heya mate,
Here is your answer,. ⬇️⬇️
![{ANSWER :-} {ANSWER :-}](https://tex.z-dn.net/?f=+%7BANSWER+%3A-%7D+)
_________
a) 25a^2b^2 - 49c^2
= (5ab)^2 - (7c)^2
= (5ab + 7c) (5ab - 7c) ⬅️
b) p^8 - q^8
= (p^4 + q^4) (p^4 - q^4)
= (p^4 + q^4) (p^2 + q^2) (p^2 - q^2)
= (p^4 + q^4)(p^2 + q^2)(p+q)(p-q) ⬅️
_________
Hope this helps,.
If helps, please mark it as brainliest ^_^
_________
REGARDS, ARNAB ✌️
THANK YOU
Here is your answer,. ⬇️⬇️
_________
= (5ab)^2 - (7c)^2
= (5ab + 7c) (5ab - 7c) ⬅️
b) p^8 - q^8
= (p^4 + q^4) (p^4 - q^4)
= (p^4 + q^4) (p^2 + q^2) (p^2 - q^2)
= (p^4 + q^4)(p^2 + q^2)(p+q)(p-q) ⬅️
_________
If helps, please mark it as brainliest ^_^
_________
REGARDS, ARNAB ✌️
THANK YOU
Similar questions